Risk factors for lung parenchyma hemorrhage and hemoptysis during computed tomography‐guided microwave ablation in patients with stage I non‐small cell lung cancer: A bicentric retrospective study - Jingshuo Li; Ziqi Zhang; Yuxian Chen; Chunhai Li; Zhigang Wei; Haipeng Jia (Thoracic Cancer)
Abstract Objectives This study aimed to identify the risk factors for lung parenchyma hemorrhage and hemoptysis during computed tomography‐guided microwave ablation (MWA) in patients with stage I non‐small cell lung cancer (NSCLC). Methods A total of 417 patients from two medical centers were included, of whom 353 were from center 1 and 64 were from center 2. The risk factors for lung parenchyma hemorrhage and hemoptysis were selected by univariable and multivariable logistic analyses in the center 1 dataset. The selected risk factors were validated in the center 2 dataset. Results The risk factors for lung parenchyma hemorrhage during MWA were focal blood supplies (odds ratio [OR], 2.602; 95% confidence interval [CI], 1.609–4.210; p < 0.001), near vessels larger than 2 mm (OR, 4.145; 95% CI, 1.963–8.755; p < 0.001), and traversing vessels in the track of ablation (OR, 2.961; 95% CI, 1.492–5.874; p = 0.002). The risk factors for hemoptysis were lung parenchyma hemorrhage (OR, 34.165; 95% CI, 12.255–95.247; p < 0.001), needle track traversing the lung parenchyma by >25 mm (OR, 4.494; 95% CI, 1.833–11.018; p = 0.001), and traversing vessels in the track of ablation (OR, 5.402; 95% CI, 2.269–12.865; p < 0.001). Conclusions Focal blood supplies, near vessels larger than 2 mm, and traversing vessels in the track of ablation were independent risk factors for lung parenchyma hemorrhage during MWA. Lung parenchyma hemorrhage, needle track traversing the lung parenchyma by >25 mm, and traversing vessels in the track of ablation were independent risk factors for hemoptysis during MWA.